Image analysis of 2-dimensional root system architecture - Leitner, Daniel; Schnepf, Andrea (Proceedings of the Conference Algoritmy, 2015)
Root system architecture is essential for plant nutrient and water uptake and is therefore crucial for plant  development. Root system responses to heterogeneous soil conditions are of highest interest in plant  nutrition, plant hydrology as well as plant breeding. An entire quantication of these root responses i.e.  phenotypical expressions calls for (a) elaborate experimental work (b) appropriate imaging techniques (c)  advanced image analysis. In the last years there has been enormous progress in imaging techniques in  terms of cost and image resolution, while there has been less progress in automated data evaluation. In this work we want to discuss existing as well as new ideas how to analyse 2-dimensional images of root system architecture, and how to extract relevant parameters describing it.